(untitled) (Bulletin KNOB, 1992)
About 1700 a sober noble man’s house called ’Hackfort’ was built on the place of a ruinous castle surrounded by a canal in the province of Gelderland near Barneveld. The house and property probably owed this name to the scenery. In the 17th century the country seat was known as ’De Schaffelaar’ by a supposed relationship with the hero Jan van Schaffelaar, who leapt from the tower in Barneveld during the so-called ’Hoekse and Kabeljauwse twisten’ (quarrels) in 1482. In 1767 one started the building of a house in Louis-XVI style on the same location. Between 1767 and 1793 a garden was laid out in Anglo-Chinese style in the direct surroundings of the house. Also the rest of the estate was embellished at the time. The oldest laying-out of avenues at right angles probably dates from the second half of the 17th century. An extension in the form of a starred wood must have taken place between the twenties and sixties of the 18th century. The connection with the landscape played an important role at laying-out. This becomes evident from the integration of farming-land, orchards and farms. Representative and economic use herewith are united at this country seat. In the winter of 1799 the house burnt down. Baron van Zuylen van Nievelt bought the country seat in 1808 and took the English landscape style as starting point for renewal. Between 1808 and 1852 an already present watercourse was changed into a ’natural’ landscape-element, a so-called ’winding pond’ and the meanwhile unexplored field, where the former house was built, was taken up in the laying-out as an island. In addition a family grave, a ’flower hill’ and duck-pipe were laid out and the starring wood was extended. The sober laying-out fits into the changing attitude around 1800 whereby exuberant elements - as at the Anglo-Chinese laying-out - were avoided and elements to be considered characteristic of Dutch agricultural nature were used at the laying-out of the park. This also perfectly fitted the extant laying-out of De Schaffelaar. From 1840 one started to design a new house on the estate. Here a clear development of thoughts can be distinguished, whereby acquaintance with the revival of the gothic style with belonging philosophies in England played an important role. As a consequence of this, in 1852 the building of a neo-gothic castle was started on the south-west part of the estate. Both the ’castellated character’ and the changed site refer to the connection of the estate and his inhabitants with nature and Barneveld’s past. In 1853 the Zochers were commissioned to design a garden in the castle’s direct surroundings. The combination of neo-gothic ’castle’ and laying-out of the landscape into a picturesque unit stresses the reference to nature and the past. The way an ideal image here has been created makes De Schaffelaar a unique monument in the Netherlands.